High-Resolution, High-Throughput, Positive-Tone Patterning of Poly(ethylene glycol) by Helium Beam Exposure through Stencil Masks - Cacao, Eliedonna E. (Public Library of Science, 2013)
In this work, a collimated helium beam was used to activate a thiol-poly(ethylene glycol) (SH-PEG) monolayer on gold to selectively capture proteins in the exposed regions. Protein patterns were formed at high throughput by exposing a stencil mask placed in proximity to the PEG-coated surface to a broad beam of helium particles, followed by incubation in a protein solution. Attenuated Total Reflectance–Fourier Transform Infrared Spectroscopy (ATR–FTIR) spectra showed that SH-PEG molecules remain attached to gold after exposure to beam doses of 1.5–60 µC/cm(2) and incubation in PBS buffer for one hour, as evidenced by the presence of characteristic ether and methoxy peaks at 1120 cm(−1) and 2870 cm(−1), respectively. X-ray Photoelectron Spectroscopy (XPS) spectra showed that increasing beam doses destroy ether (C–O) bonds in PEG molecules as evidenced by the decrease in carbon C1s peak at 286.6 eV and increased alkyl (C–C) signal at 284.6 eV. XPS spectra also demonstrated protein capture on beam-exposed PEG regions through the appearance of a nitrogen N1s peak at 400 eV and carbon C1s peak at 288 eV binding energies, while the unexposed PEG areas remained protein-free. The characteristic activities of avidin and horseradish peroxidase were preserved after attachment on beam-exposed regions. Protein patterns created using a 35 µm mesh mask were visualized by localized formation of insoluble diformazan precipitates by alkaline phosphatase conversion of its substrate bromochloroindoyl phosphate-nitroblue tetrazolium (BCIP-NBT) and by avidin binding of biotinylated antibodies conjugated on 100 nm gold nanoparticles (AuNP). Patterns created using a mask with smaller 300 nm openings were detected by specific binding of 40 nm AuNP probes and by localized HRP-mediated deposition of silver nanoparticles. Corresponding BSA-passivated negative controls showed very few bound AuNP probes and little to no enzymatic formation of diformazan precipitates or silver nanoparticles.